2018
DOI: 10.1111/hiv.12595
|View full text |Cite
|
Sign up to set email alerts
|

BCN Checkpoint: same‐day confirmation of reactive HIV rapid test with Point Of Care HIVRNA accelerates linkage to care and reduces anxiety

Abstract: Background The introduction in 2006 of the rapid HIV test by BCN Checkpoint in a non‐clinical setting has been a successful step forwards in the uptake of testing. Nevertheless, HIV serostatus should be reported as HIV positive only when a reactive result has been tested again using a different assay (WHO guidelines 2015). The standard confirmation test has been the Western Blot (WB) test. However confirmation results take around 7 days to come back. Aims This study explores the possibility of Point of Care PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…The proportion of HIV-positive infants who were initiated on ART by 60 days increased from 43.3% to 92.3%, with cost per result returned in 30 days decreasing from $131 (U.S. dollars) with conventional referral laboratory testing to $38 with POC testing. In a study for diagnosing acute HIV infection, 91% of the patients attending a community clinic in Spain were notified of their HIV-positive status the same day using the Xpert HIV-1 Qual assay (126). These studies demonstrate that POC platforms can be successfully implemented in a number of settings and have led to guidelines for the introduction of HIV POC diagnostics into national programs (127).…”
Section: Evidence and Results From Clinical Studiesmentioning
confidence: 99%
“…The proportion of HIV-positive infants who were initiated on ART by 60 days increased from 43.3% to 92.3%, with cost per result returned in 30 days decreasing from $131 (U.S. dollars) with conventional referral laboratory testing to $38 with POC testing. In a study for diagnosing acute HIV infection, 91% of the patients attending a community clinic in Spain were notified of their HIV-positive status the same day using the Xpert HIV-1 Qual assay (126). These studies demonstrate that POC platforms can be successfully implemented in a number of settings and have led to guidelines for the introduction of HIV POC diagnostics into national programs (127).…”
Section: Evidence and Results From Clinical Studiesmentioning
confidence: 99%
“…Twenty studies provided non‐targeted testing to the general population, while 44 studies provided testing to one or more groups at higher risk of HIV infection. MSM were the group most frequently targeted ( n = 31) , followed by: migrants ( n = 10) , people who use/inject drugs (PWUD/PWID) ( n = 8) , SWs ( n = 7) , black and minority ethnic groups (BME) ( n = 5) , young people ( n = 4) , homeless people ( n = 3) , and other key risk populations not specified ( n = 3) .…”
Section: Resultsmentioning
confidence: 99%
“…An overview of these 80 studies can be found in Table . Studies were from 14 of the 30 countries in the EU/EEA, with most set in Northern Europe ( n = 37), followed by Southern Europe ( n = 27) and Western Europe ( n = 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations